Endothelial dysfunction in patients with various forms of congenital epidermolysis bullosa - V. I. Kornev; O. N. Startseva; A. S. Pleshkov; M. V. Nikiforov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The endothelial system is an important component of vascular-platelet hemostasis, capable of actively responding to mechanical and inflammatory agents. Patients with congenital epidermolysis bullosa are prone to mechanical damage to the skin and the development of a chronic inflammatory syndrome with a high probability of endothelial dysfunction.The study objective was to assess the state of the endothelial system and to reveal the dependence of endothelial dysfunction on the form of epidermolysis bullosa.Methods and materials. The study used venous blood of 57 patients (27 men and 30 women) with congenital epidermolysis bullosa. In patients with simple and dystrophic forms of epidermolysis bullosa, the platelet count, P-selectin, fibrinogen, albumin, C-reactive protein, von Willebrand factor antigen concentration, and factor VIII activity were determined.Results. Comparative results of endothelial dysfunction depending on the form of epidermolysis bullosa were represented and endothelial dysfunction’s dependence on the concentration of albumin, C-reactive protein, and platelet count was determined.Conclusions. In patients with a dystrophic form of epidermolysis bullosa, endothelial dysfunction is accompanied by an increase in the expression of P-selectin, factor VIII activity, and the concentration of von Willebrand factor antigen. Chronic inflammation and impaired nutritional status with a decrease in albumin contribute to the development of endothelial dysfunction.